Faktor-Faktor Yang Mempengaruhi Tingkat Keparahan Korban Kecelakaan Lalu Lintas Di Kota Padang Menggunakan Analisis Regresi Logistik Ordinal - roza maylinda; dony permana (Journal of Mathematics UNP, 2019)
Abstract — Traffic accident are problem that requires serious treatment based of the large losses. The increase in traffic amount in Padang as the prove. This research goals are the factors that influence the severity of traffic accident victims. Dependent variables in the form of ordinal data are minor injuries, serious injuries, and death. The independent variables are the age of the victim, sex, type of accident, the role of the victim, and the type of vehicle. Ordinal logistic regression analysis will be used to analyze the independent variables that are corrected the severity of traffic accidents at Padang in 2018. Data obtained from the Lakalantas Padang Police Unit. Based on the results of the analysis obtained the age of victim, the type of accident, and the type of vehicle become a factor in the severity of traffic accident victims in Padang.Keywords — Traffic Accident, The Severity, Ordinal Logistic Regression